Studying the Effect of Some Factors on Productivity of Buffalo Milk in Al-Ghab Plain - Naddaf, Tawfik (Latakia University Journal -Biological Sciences Series, 2013)
This study aimed atevaluating the effect of calving season, age at first calving, age at first conception, and finally the effect of first calving-first conception interval on the milk production of buffaloes in Al-Ghab Plain. The study is based on data collected from a number of farms for breeding swamp buffaloes in Al-Gab Plain. The data was collected for one season starting from the beginning of spring 2010. The study was conducted on 33 buffaloes aging between 3-9 yearsand weighing 36-550 kg (average 420kg) and over different seasons starting with the first season till the fifth one. The results showed that the total amountof buffalo milk was on average 1421 kg; and the best females were those with 50 days calving-conception interval;the age at first conception was 20 months; the age at first calving was 30.14 months; and finally most calvings occurred in spring(seasonal calvings).